Identification of a Novel Bcl-2 Inhibitor by Ligand-Based Screening and Investigation of Its Anti-cancer Effect on Human Breast Cancer Cells - Wen, Mei; Deng, Zhen-ke; Jiang, Shi-long; Guan, Yi-di; Wu, Hai-zhou; Wang, Xin-luan; Xiao, Song-shu; Zhang, Yi; Yang, Jin-ming; Cao, Dong-sheng; Cheng, Yan (Frontiers in Pharmacology, 2019)
Bcl-2 family proteins are key regulators of apoptosis that is implicated in many human diseases, particularly cancer. The anti-apoptotic proteins of Bcl-2 family, such as Bcl-2, are overexpressed in numerous cancers and contribute to tumor initiation, progression and resistance to therapy. Therefore, Bcl-2 is an attractive target for drug development, and several Bcl-2 inhibitors are currently undergoing clinical trials. In this study, we carried out a QSAR-based virtual screening approach to develop potential Bcl-2 inhibitors from the SPECS database. Surface plasmon resonance (SPR) binding assay was performed to measure the interaction between Bcl-2 protein and the screened inhibitors. After that, we measured the anti-tumor activities of the 8 candidate compounds, and found that compound M1 has significant cytotoxic effect on breast cancer cells. We further proved that compound M1 downregulated Bcl-2 expression and activated apoptosis by inducing mitochondrial dysfunction. In conclusion, we identified a novel Bcl-2 inhibitor by QSAR screening, which exerted significant cytotoxic activity in breast cancer cells through inducing mitochondria-mediated apoptosis.